Determinants of Zakat, Infaq, and Shadaqah at Lazismu East Java: Reputation, Religiosity, Trust, Ease, Security and Convenience - Wiwit Hariyanto; Sigit Hermawan; Ali Zainuri Rahmadhani; Sintha Wahyu Arista; Zatul Karamah Ahmad Baharul Ulum (el-Jizya: Jurnal Ekonomi Islam, 2025)
The management of the Muhammadiyah Zakat, Infaq and Alms Institution (Lazismu) in East Java needs to know the reasons why muzaki or donors pay ZIS at the institution. This is related to the performance of services that must be carried out so that they are right on target and provide satisfaction to Muzakki. This study aims to improve the performance of services to Muzaki who have entrusted their zakat, infaq and alms (ZIS) funds to Lazismu East Java. The research method chosen is quantitative research with a descriptive and causal approach. The population of this study was all muzaki who had distributed ZIS at Lazismu in East Java. The determination of the sample used purposive sampling, while the sample in this study was 110 respondents. The results of this study are the determining factors including reputation factors, religiosity factors, trust factors, ease factors, and security and convenience factors that have a positive influence on the decision of muzaki to pay ZIS at Lazismu East Java. In this study, the convenience variable is the strongest and most dominant variable while the reputation variable is the weakest variable in Muzaki's decision to choose ZIS at Lazismu East Java. By understanding and optimizing these five factors, Lazismu East Java can increase muzaki loyalty, improve performance and strengthen its role in supporting social and economic programs that are in line with the objectives of the Sustainable Development Goals (SDGs) Number 8 concerning decent work and economic growth.